2016
DOI: 10.14434/josotl.v16i3.19268
|View full text |Cite
|
Sign up to set email alerts
|

A Curricular Intervention for Teaching and Learning: Measurement of Gains of First-Year Student Learning

Abstract: There is continued debate about the changing and varied nature of first year courses in American higher education institutions. Therefore more current research is needed to inform faculty and institutions as to the important areas of focus for teaching and learning in first year courses. This study is one possible approach to easily determine student “gains” as described by measured improvements in the selected areas. The purpose of this paper was to examine the observed gains of first year experience course s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The most powerful finding of this study is reflected in the fact that course participants displayed a statistically significant improvement in academic attitudes and behaviors for all 10 factors. This finding corroborated the work of Cox and Lemon (2016) who recorded statistically significant pre and post-tests differences for FYS participants within the same institution. Even though this study was conducted five years later, on a different sample of participants, and under a redesigned curriculum, the findings were equally powerful.…”
Section: Discussionsupporting
confidence: 89%
“…The most powerful finding of this study is reflected in the fact that course participants displayed a statistically significant improvement in academic attitudes and behaviors for all 10 factors. This finding corroborated the work of Cox and Lemon (2016) who recorded statistically significant pre and post-tests differences for FYS participants within the same institution. Even though this study was conducted five years later, on a different sample of participants, and under a redesigned curriculum, the findings were equally powerful.…”
Section: Discussionsupporting
confidence: 89%
“…Self-efficacy has also been applied in a number of learning gain studies (e.g. Arico, 2016;Cox & Lemon, 2016;Lim, Hosack, & Vogt, 2012) which have used students' self-assessment of their learning, knowledge and/or skills and demonstrated that students' self-assessment of their learning can provide a robust measure of learning. Ongoing application of these measures in classroom settings (as explored, for example by Arico, 2016) have demonstrated learning gain over time.…”
Section: Research Methods and Their Role In Undergraduate Educationmentioning
confidence: 99%
“…Attempts to capture learning gain have been shaped by a variety of definitions and methodological approaches (e.g. Corlu & Aydin, 2016;Cox & Lemon, 2016;Lim et al, 2012;Varsavsky et al, 2014), which make comparative work in this area challenging to undertake (McGrath et al, 2015).…”
Section: Developing Connections Between Learning Gain and Research Methodsmentioning
confidence: 99%
“…Paid employment hours could be simultaneously helpful for student learning by creating a framework for knowledge or skills connection 33,34 while at the same time having a negative effect on available study time. Required employment hours may also stimulate more effective study habits 35 or have a threshold effect on week quality, with most of our students staying below that critical threshold. We continue to collect data for more analysis and verification of our findings.…”
Section: Question 4a: Were Week Quality Scores Correlated With Sleepmentioning
confidence: 99%